Heterologous expression, characterisation and 3D-structural insights of GH18 chitinases derived from sago palm (Metroxylon sagu) - Hairul Azman, Roslan; Md Anowar, Hossain (Elsevier B.V., 2024)
Although plants don’t have chitins, they produce chitinases to protect themselves from biotic and abiotic stressors. There are two forms of chitinases found in organisms: glycosyl hydrolase 18 (GH18) and 19 (GH19) families. Plant GH19 chitinases are well known for their role in protecting against pathogens, but the roles of GH18 chitinases have not been fully elucidated. This study aimed to produce and characterise two recombinant GH18 chitinases from Metroxylon sagu. Two GH18 chitinase genes, MsChi1 and MsChi2, were identified, with nucleotide sequences of 1009 and 1308 bp, respectively. The proteins encoded by MsChi1 and MsChi2 genes were single polypeptide chains of 310 and 300 amino acids with predicted molecular masses of 31.21 and 30.15 kDa, respectively. Both cDNAs were cloned and expressed in the GS115 strain of Pichia pastoris. Recombinant MsChi1 and MsChi2 exhibited optimal activity at 60 ◦C with acidic pH 4.0 and 5.0, respectively. Both recombinant enzymes could hydrolyze synthetic and natural substrates (colloidal chitin). rMsChi1 preferred 4-nitrophenol N,N′-diacetyl-β-D chitobioside, while rMsChi2 preferred 4-nitrophenol N,N′,N″-triacetyl-β-D chitotriose, suggesting they might function as exochitinase and endochitinase, respectively. They also demonstrated antifungal activities against tested fungi. Homology modeling indicated ASP and GLU as essential residues for proton donation and acceptance.